Modification of Sugar Profile and Ripening in Atemoya (Annona × atemoya Mabb.) Fruits through Copper Hydroxide Application - Cardoso, Caroline P. [UNESP]; Campos, Felipe G. [UNESP]; Napoleão, Gabriel M. [UNESP]; Barzotto, Gustavo R. [UNESP]; Campos, Lauro P. [UNESP]; Ferreira, Gisela [UNESP]; Boaro, Carmen S. F. [UNESP] (MDPI, 2023)
Atemoya (Annona × atemoya Mabb.), a climacteric fruit of the Annonaceae family, is becoming increasingly popular due to its organoleptic and nutritional properties. Anthracnose, a fungus of the Colletotrichum genus, is one of the most serious diseases in orchards, causing significant damage if not controlled, so producers use phytosanitary products. The current study sought to investigate the quality of atemoya fruits after harvest in an orchard with anthracnose controlled by Cu(OH)2 application: T1—no Cu(OH)2, T2—7.8 mL Cu(OH)2 L1 divided into two applications, T3—15.6 mL Cu(OH)2 L1 divided into four, T4—8.0 mL Cu(OH)2 L1 divided into eight, and T5—13.0 mL Cu(OH)2 L1 divided into thirteen applications. The sugar profile of fruits was examined, as well as MDA, H2O2, and quality parameters such as pH, mass, soluble solids, titratable acidity, and maturation index. MDA, such as H2O2, can function as a signal molecule. Eight applications of 1.0 mL L-1 Cu(OH)2 resulted in increased concentrations of H2O2 and MDA, signal molecules involved in sugar modification profiles such as glucose, fructose, and trehalose. It also had a high titratable acidity, a lower maturation index, better fruit quality, and a longer shelf life.
Keywords: carbohydrates; cupric fungicide; custard apple; maturation index